2019
DOI: 10.1071/an18286
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing 2 g per day bovine lactoferrin from late gestation until weaning did not improve lactation performance of mixed parity sows

Abstract: Context Lactoferrin is a non-haem binding protein that possesses antimicrobial, antioxidant and anti-inflammatory properties. A previous study showed lactoferrin supplementation from early gestation to weaning improved lactation performance in primiparous sows; however, it is unknown whether the supplementation within a more specified duration (from late gestation to weaning) can improve lactation performance in multiparous sows, which limits its commercial application. Aims This experiment investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…We found that sows mated in summer were 20 kg lighter at mating than those mated in autumn, which is likely to be a consequence of negative energy balance during summer lactation [ 30 , 31 ]. Similarly, in our previous lactation studies conducted in summer and autumn, we observed that sows lactating in summer had 15% lower ADFI and 33 kg less body weight at weaning than those lactating in autumn [ 32 , 33 ]. The restricted amount of energy allowance during gestation might have to be distributed towards maternal tissue recovery, thus nutrient allocation to the conceptus could be affected.…”
Section: Discussionsupporting
confidence: 73%
“…We found that sows mated in summer were 20 kg lighter at mating than those mated in autumn, which is likely to be a consequence of negative energy balance during summer lactation [ 30 , 31 ]. Similarly, in our previous lactation studies conducted in summer and autumn, we observed that sows lactating in summer had 15% lower ADFI and 33 kg less body weight at weaning than those lactating in autumn [ 32 , 33 ]. The restricted amount of energy allowance during gestation might have to be distributed towards maternal tissue recovery, thus nutrient allocation to the conceptus could be affected.…”
Section: Discussionsupporting
confidence: 73%
“…indicates that the high weight loss group created for our current experiment might not have been affected severely enough to influence the subsequent farrowing rate. The amount of feed intake during a summer lactation in the current experiment was 18% lower than that reported at the same research facility during a cool season (autumn) (Liu et al, 2019), and this magnitude of reduction in lactational feed intake agrees with other observations that Australian summer conditions usually reduces voluntary feed intake of lactating sows by 17% (Lewis and Bunter, 2011). Another possible reason for the lack of change in the subsequent reproductive performance between the HLStd and LLStd sows is the increasing resilience to lactational catabolism of prolific sows due to genetic selection.…”
Section: Discussioncontrasting
confidence: 74%
“…An earlier study has demonstrated the beneficial effects of supplementing preterm piglets with 0.1 to 1 g/d of bovine milk derived LF on intestinal growth, development, and protection from disease (Nguyen et al, 2014). However, supplementation of LF to mixed parity sows at 2 g/d from late gestation to weaning did not improve lactation performance (Liu et al, 2019). Therefore, dose and duration are 2 important factors that need to be considered during LF supplementation.…”
Section: Discussionmentioning
confidence: 99%